Colonoscopy performed with selective use of sedation: A case report - M Tun (South African Medical Journal, 2022)
Colonoscopy is the gold standard for diagnosis of colonic disease. We present a patient with chronic diarrhoea and a caecal tumour that was diagnosed with colonoscopy.